Social Value Orientation and Endorsement of Horizontal and Vertical Individualism and Collectivism: An Exploratory Study Comparing Individuals From North America and South Korea - Moon, Chanki; Travaglino, Giovanni A.; Uskul, Ayse K. (Frontiers in Psychology, 2018)
Individuals’ cultural tendencies of horizontal/vertical individualism and collectivism interact with their dispositional traits and contextual factors to shape social interactions. A key dispositional trait is social value orientation (SVO), a general tendency towards competition (proself) vs. cooperation (prosocial) in social exchanges. The present study (N = 1032) explored the relationship between SVO and personal cultural tendencies of horizontal/vertical individualism and collectivism in two different cultural settings, the US (a vertical individualist setting) and South Korea (a vertical collectivistic setting). We hypothesized that each value orientation would be associated with the congruent personal cultural tendency across settings. We further hypothesized that this association would be specific to the context, so that SVO would play a more relevant role where the cultural theme was less dominant. Results indicated that, across contexts, proself individuals endorsed vertical individualistic values more strongly than prosocial individuals. Conversely, prosocial individuals endorsed horizontal collectivistic values more strongly than proself individuals. In addition, the effect of SVO was different in the two cultural contexts. Compared to proself individuals, prosocial individuals endorsed horizontal collectivism more strongly in the US context, and horizontal individualism less strongly in the Korea context. Theoretical implications and limitations of the findings, as well as directions for future work are discussed.